LOVE AND BELONGING NEEDS OF MAIN CHARACTER IN NOVEL “ME BEFORE YOU” BY JOJO MOYES - Ruth, Grace; Satria, Robby (LPPM Universitas Putera Batam, 2020)
The research emphasizes on the analysis of Hierarchy of needs tiers and love and belonging needs that found in “Me Before You” novel by Jojo Moyes. The story in this novel begin from Louisa as a family breadwinner who had to work to fulfill economy needs, looking after William who was seriously ill and disability. The object of the research is love and belonging needs in “Me Before You” novel by Jojo Moyes viewed from Abraham Maslow Hierarchy needs theory. The researcher employs qualitative descriptive method. In doing this qualitative research, the reseacher used a love and belonging needs theory purpose by Abraham Maslow. The researcher would be explained three of love and belonging needs that found in this novel. Those are from family, friends and intimacy love. All of these love and belonging needs have their own meaning to symbolize a situation or feeling of character in this novel. After that, the researcher found the obstacle and struggle of main charachter to fulfill love and belonging needs to the story in that novel. From the analysis, it can be concluded the love and belonging needs to be found in